2021
DOI: 10.1038/s41598-021-81545-5
|View full text |Cite
|
Sign up to set email alerts
|

Early bilingual experience is associated with change detection ability in adults

Abstract: To adapt to their more varied and unpredictable (language) environments, infants from bilingual homes may gather more information (sample more of their environment) by shifting their visual attention more frequently. However, it is not known whether this early adaptation is age-specific or lasts into adulthood. If the latter, we would expect to observe it in adults who acquired their second language early, not late, in life. Here we show that early bilingual adults are faster at disengaging attention to shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In addition, the long-range implications of monolingual-bilingual differences in the distribution of attention remain undetermined. In view of recent research showing increased attentional shifting in bilingual adults who acquired both languages early in life (D'Souza, Brady, Haensel, & D'Souza, 2021), one question is whether effects of bilingualism on visual exploration extend to other learning behaviors. For example, when navigating their environment, some adults continually pursue new information (termed busybodies) and others seek to further their expertise within familiar domains (termed hunters).…”
Section: The Road Aheadmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the long-range implications of monolingual-bilingual differences in the distribution of attention remain undetermined. In view of recent research showing increased attentional shifting in bilingual adults who acquired both languages early in life (D'Souza, Brady, Haensel, & D'Souza, 2021), one question is whether effects of bilingualism on visual exploration extend to other learning behaviors. For example, when navigating their environment, some adults continually pursue new information (termed busybodies) and others seek to further their expertise within familiar domains (termed hunters).…”
Section: The Road Aheadmentioning
confidence: 99%
“…Further studies could also address whether other environmental factors (e.g., variation in parenting practices) contribute to a novelty orientation. For example, bilingual children are often raised by bilingual parents who may direct their children's attention more broadly within the environment given evidence that bilingual adults explore their own environment more broadly (D'Souza et al, 2021). In this way, a novelty orientation in bilingual children could be coregulated by children and their caregivers.…”
Section: The Road Aheadmentioning
confidence: 99%
“…Neuroimaging studies suggest that EF control mechanisms are crucial when alternating attention between tasks and languages. Most of the evidence comes from young adult populations, but a recent study indicates that the effects may also be present during infancy (D'Souza et al, 2021). Similarly, the literature on divided attention is scarce, making it difficult to determine whether bilingualism influences this type of attention.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent research with infants has shown that infants exposed to a bilingual environment are better at shifting attention to a novel stimulus and alternate attention more frequently than infants exposed to a monolingual environment (D'Souza et al, 2020). These early adaptations to the attentional system during infancy have been found to persist into adulthood (D'Souza et al, 2021). Hence, bilinguals have an edge in situations requiring flexibly switching attention between tasks to meet the demands of their rapidly changing environment.…”
Section: Alternating Attentionmentioning
confidence: 99%
“…D’Souza et al (2021) investigated similar processes in monolingual and bilingual adults. The authors separated their bilingual sample by the age of acquisition of both languages, distinguishing behavioral patterns evidenced in early bilinguals from late bilinguals.…”
mentioning
confidence: 99%